Luminescence ring formation in quantum wells - a model with Coulomb interaction - Denev, S; Simon, S; Snoke, D (2005)
The appearance of a luminescence ring around a central illumination spot in quantum well structures is now well understood in terms of charge separation between the electron and hole gasses in the quantum well region with the ring appearing at their boundary. We propose a slightly modified model including Coulomb interaction between the electron and hole gas and their image charge. © 2005 Elsevier Ltd. All rights reserved.